Implementation of Electronic-Based Government Procurement of Goods and Services at the Department of Communications, Informatics, and Statistics of Wajo Regency - Syamsiar Syamsiar; Besse Herlina; Muhammad Nur; Tenri Dio (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the implementation of electronic-based government procurement of goods and services at the Department of Communications, Informatics, and Statistics of Wajo Regency and to identify the supporting and inhibiting factors affecting its implementation. The research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving the Head of Department, structural officials, implementing officers, and service providers engaged in the procurement process. The findings reveal that the implementation of electronic-based procurement has generally been effective. Communication and coordination among stakeholders have been carried out through socialization programs, meetings, and technical assistance activities. Adequate human resources and information technology infrastructure have supported the implementation of procurement through the Electronic Procurement System (SPSE). Furthermore, the commitment of implementers to complying with procurement regulations and procedures has contributed to a procurement process that is more transparent, efficient, effective, and accountable. The bureaucratic structure has also functioned in accordance with established duties and work mechanisms. Supporting factors include good coordination among implementers, personnel competence in operating the electronic procurement system, adequate technological infrastructure, and transparency of procurement information. However, several obstacles remain, such as internet network disruptions, technical problems within the application system, and the need to enhance personnel capacity in adapting to the continuous development of electronic procurement systems and regulations.